The Effects of Cold Water Immersion on the Recovery of Drop Jump Performance and Mechanics: A Pilot Study in Under-20 Soccer Players - Kositsky, Adam; Avela, Janne (Frontiers in Sports and Active Living, 2020)
Cold water immersion (CWI) is a popular method used for enhancing recovery from exercise. However, the efficacy of this approach is inconclusive and studies investigating variables contributing to overall performance are scarce. Additionally, few studies have investigated the recovery of stretch-shortening cycle (SSC) performance after a fatiguing SSC task. The SSC occurs naturally in human locomotion and induces a recovery pattern different from isolated muscle contractions (e.g., pure eccentric exercise). Therefore, the main aim of this study was to investigate the effects of a single CWI on jumping performance and mechanics after exhaustive SSC exercise. On a sledge apparatus, ten male under-20 soccer players (age 18-20 years) performed five sets of 20 maximal drop jumps (DJ) followed by continuous submaximal rebounding. Subjects were equally randomized into a passive recovery control (CON) or CWI group (10±0.5°C for 20 minutes). Prior to, upon completion of, and at 24 (24H) and 48-hour (48H) follow-ups, subjects performed maximal DJs recorded with a high-speed video camera. Blood samples were taken and subjective muscle soreness was measured. Rebound jump height was impaired immediately after exercise, although significant only for CWI (CON: -12.4 cm, p = 0.083; CWI: -9.9 cm, p = 0.009). The CWI group demonstrated significant recovery of jump height at 24H (+6.3 cm, p = 0.031) and 48H (+8.9 cm, p = 0.002) compared to post-exercise. Ankle joint stiffness was decreased for CWI (-2.1 to -2.5 Nm/deg, p = 0.005-0.041). Creatine kinase activity was similarly increased for both groups at 24H and 48H, while there was also no group effect in muscle soreness (p ≥ 0.056). This pilot study demonstrates the potential for CWI to slightly enhance the recovery of DJ performance. However, this occurred in parallel with reduced ankle joint stiffness, signifying that jumps were performed with less efficiency, which would not be favourable for repeated SSC actions. While this should be confirmed with a larger sample size, this highlights the potential for CWI to be detrimental to the mechanical properties of the ankle joint. Therefore, future recovery intervention studies should concomitantly investigate variables contributing to performance, rather than just overall performance itself.